Antenatal corticosteroids for preterm births in resource-limited settings - Authors' reply - Althabe, Fernando (2015)
We have several comments regarding the letters about our study. First, Gerard Visser andGian Carlo DiRenzo state that if corticosteroids are given appropriately they can reduce perinatalmorbidity and mortality, whereas inappropriate use is likely to be harmful. However, the evidenceshowing that corticosteroids reduce neonatal morbidity and mortality are from studies done in hospitals in high-income and middle-income countries with good newborn care. By contrast, our antenatal corticosteroid trial (ACT)1 was done in low-income and middle-income countries,evidence showed no benefit with use of this drug. Therefore, the setting of where the drug is used matters.